Farm barns - Harrison, Raymond D. (My University, 1906)
Introduction: In the construction of farm buildings, the barn stands second in importance, and in writing this treatise upon the subject it has been my intention to draw the plans of several barns and write, the specifications for one barn which would meet the general requirements of the modern and scientific farmer. The one for which the following specifications are written is a general farm barn, in which is included a carriage and implement shed and which is arranged to accommodate both horses and cattle. One feature quite advantageous to its floor plan is that the horses and cows may be easily separated by simply closing the door joining the two stables which will not affect the ventilation of either. The roof extending over the carriage room gives an abundance of hay room which is a very desirable feature. The carriage room is furnished with a carriage and horse wash so that each may be easily and economically cleaned while the mud is yet soft. One of the most important questions in building is the choosing of a site. A location to be ideal must have at least three qualifications: proper surface drainage, nearness to water, and convenience to the house and road.
Citation: Harrison, Raymond D. Farm barns. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Construction; Barns; Building Specifications; Site Selection; Theses